Pengaruh Pemberian Edukasi terhadap Pencegahan dan Deteksi Dini Penyakit Kanker Payudara pada Ibu-Ibu Majelis Al-‘Arabiyyat Kota Palu - Andi Atirah Masyita; Amelia Rumi (Jurnal Pengabdian Pada Masyarakat, 2021)
THE EFFECT OF EDUCATION ON PREVENTION AND EARLY DETECTION OF BREAST CANCER IN MAJELIS AL-‘ARABIYYAT MOTHER, PALU CITY. Breast cancer has a high prevalence. Breast cancer patients often come with an advanced stage so that the prognosis is poor, because at least women do early detection for breast cancer at an early stage. This study aims to increase public knowledge about the importance of routine breast self-examination (BSE) for early detection of breast cancer. The method used for problem solving in this activity is education followed by discussion. This activity was attended by 50 participants consisting of women reciting the Al-'Arabiyyat recitation. The results of the research on the level of BSE knowledge before and after education experienced an increase in knowledge from 6.67 to 7.72 using the paired sample t-test, the statistical test results obtained by a value of p = 0.011, this shows a change in knowledge about BSE before and after education. Conclusion: The effect of education is very effective in increasing the knowledge of assembly women about BSE as an early detection of breast cancer in majelis al-‘arabiyyat, the city of Palu.